ANALYSIS OF SOCIOECONOMIC FACTORS ON HEALTHCARE FACILITIES UTILIZATION FOR INPATIENT CARE IN INDONESIA - Mutia Narullita Anwar; Pujiyanto Pujiyanto (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
In 2014-2018 the utilization of health facilities for inpatient treatment in Indonesia has ups and downs. according to data from the National Social Security Council (DJSN) and Social Security Administrator for Health (BPJS Kesehatan) in 2020, the average unit cost of claims per first-level inpatient admission nationally in 2014-2018 were Rp420,543, Rp323,687, Rp412,512, Rp531,496, and Rp472,984, respectively. The purpose of this study was to determine the socioeconomic factors that influence the utilization of health facilities for inpatient treatment in Indonesia. This study uses secondary data from the National Socio-Economic Survey (Susenas) in 2020. The research respondents were individuals who were randomly selected as many as 1,258,328 in Indonesia. The method used in this study uses an econometric approach using the Binary Regression method, namely the logit and probit models. The results of this study found that age, education, occupation, income, and health insurance, with income assumed from the level of expenditure, all of these variables had a significant effect on the utilization of health facilities for inpatients.